Dehydration Time Effect on Tooth Color Measurement: An In Vitro Study - Ahmed, Yasmine T.; Almutairi, Fahad A.; Alomran, Shaima A.; Alkhayatt, Nourah M.; Alsulaiman, Shahad A.; Alohali, Salma Y.; Alhamdi, Albatool A. (European Journal of Dentistry, 2022)
Objectives Esthetics have become a primary influencing factor for patient satisfaction, thus dental restorations shade selection is critical, as it should closely resemble a healthy tooth. During various dental procedures, teeth are subjected to dehydration. The commonly used shade guides are being replaced with electronic color measurement devices for more precise measurements. The aim of this study was to evaluate the effect of dehydration time on tooth color measurement using a spectrophotometer.Materials and Methods Study sample is represented by 20 extracted caries-free maxillary central incisors, which were obtained from several private clinics in Riyadh, Saudi Arabia, and soaked in normal saline for 24 hours. The VITA Easyshade Advance 4.0 spectrophotometer was used to measure the color at different areas of the tooth (cervical, middle, and incisal thirds) at three time intervals (baseline, after 1 hour of dehydration, and after 2 hours of dehydration).Statistical Analysis All color coordinates across the different areas of each tooth at the incisal, middle, and cervical thirds descriptive statistics of mean (standard deviation) values were calculated and were compared at the different time intervals at baseline, after 1 hour of dehydration, and after 2 hours of dehydration. Finally, the color change value ∆E was calculated using the formula ∆E*ab = √ (L2∗ − L1∗)2 + (a2∗ − a1∗)2 + (b2∗ − b1∗)2.Results The color difference ∆E showed statistically significant changes at different time intervals: at baseline, after 1 hour of dehydration, and after 2 hours of dehydration (p < 0.001). Hue had statistically significant changes between 1 hour and 2 hours of dehydration (p = 0.002). Chroma value also showed statistically significant changes (p < 0.001) in all time intervals.Conclusion By using VITA Easyshade Advance 4.0 spectrophotometer, it was indicated that the tooth color measurements were significantly affected by dehydration time, and tooth shade appeared lighter due to changes in the refractive indices as air replaces the interprism spaces within the enamel. Tooth color measurements for shade selection should be taken as soon as possible to limit dehydration effect and ensure a more accurate shade selection for an enhanced esthetic result.
Keywords: tooth color; dehydration time; shade selection; color measurement